The Effect of performance appraisal on Job Performance in Thi-Qar and Sumer Universities - hammood, Ahmed Mohammed; Ismail, Fadillah Binti; Hamawandy, Nawzad Majeed; AL .Bewani, Hemn Adl Wali; Rahman, Shorsh Khaild; Jamil, Diyar bdulmajeed (The journal of contemporary issues in business and government, 2021)
The study aims to explore the effect of performance appraisal in Thi-Qar and Sumer Universities academic staff. The data were collected through structured questionnaires from 144 teaching staff. The findings revealed that there are positive and significant relationships between independent and dependent variables. That is establishing performance standards, communicating established standards, measuring actual performance and compare with standards, discussing the appraisal and giving feedback and indicating corrective action with teaching staff performance. Thus, for effective performance appraisal system the management of the university has to make some improvement in the appraisal system practice.